Pemanfaatan Pemrograman Visual Sebagai Sarana Pengenalan Pemrograman Komputer Untuk Pembuatan Game Edukasi - Gunawan, Dedi; Al irsyadi, Fatah Yasin (Universitas Muhammadiyah Surakarta, 2015)
Visual programming is a tools in computer programming which aims to give easy understanding in writing code program. The main users of visual programming are students and people who have no experiences in making computer code and lack of computer programming language. Visual programming gives advantages to develop any kind of application software such as game and application related to education that are the most common applications. This research was conducted to the teachers who teach Al-Quran for children learning in order to know the benefit of using visual programming in terms of creating an animation and game education. Several approach has been conducted in this research. The first is surveying the knowledge in computer programming of the research object by using questioners. Following that, we provide a training of using visual programming and the last is conduction survey in order to know the progress of study. Based on the questioner data, it can be found that visual programming is very useful to introduce computer programming for people who have limited computer background. The data shows that 60% respondent believe that the visual programming is easy to follow, while the rest says it is hard to do.